Electrical motors in the lift systems: a review - Nasir, Nur Ashikin Mohd; Shukor, Fairul Azhar Abdul; Abdullah, Norrimah; Othman, Raja Nor Firdaus Kashfi Raja (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper discussed a few type linear motors for lift systems applications. First, a few types of lift systems are generally presented. Based on these types of lift systems, the common actuators used to operate the lifts are compared and analyzed. Basically, in traditional lift systems, rotational motors are commonly employed as actuators. However, to achieve simpler lift systems, linear motors are utilized instead of rotational motors in direct drive systems. There are three types of linear motors usually being adopted which are linear induction motors (LIM), permanent magnets linear synchronous motors (PMLSM) and switched-reluctance linear synchronous motors (SRLSM). LIM exhibits a simple structure but relatively have low performance, while the SRLSM demonstrates a similar simplicity yet delivering improved performance compared to the LIM. On the other hand, the PMLSM, despite its high-performance capabilities, suffers from notable cogging.